Patterns of protective associations differ for antibodies to P. falciparum‐infected erythrocytes and merozoites in immunity against malaria in children. Issue 12 (13th September 2017) - Chan, Jo‐Anne; Stanisic, Danielle I; Duffy, Michael F; Robinson, Leanne J; Lin, Enmoore; Kazura, James W; King, Christopher L; Siba, Peter M; Fowkes, Freya JI; Mueller, Ivo; Beeson, James G
Abstract: Acquired antibodies play an important role in immunity to P. falciparum malaria and are typically directed towards surface antigens expressed by merozoites and infected erythrocytes (IEs). The importance of specific IE surface antigens as immune targets remains unclear. We evaluated antibodies and protective associations in two cohorts of children in Papua New Guinea. We used genetically‐modified P. falciparum to evaluate the importance of PfEMP1 and a P. falciparum isolate with a virulent phenotype. Our findings suggested that PfEMP1 was the dominant target of antibodies to the IE surface, including functional antibodies that promoted opsonic phagocytosis by monocytes. Antibodies were associated with increasing age and concurrent parasitemia, and were higher among children exposed to a higher force‐of‐infection as determined using molecular detection. Antibodies to IE surface antigens were consistently associated with reduced risk of malaria in both younger and older children. However, protective associations for antibodies to merozoite surface antigens were only observed in older children. This suggests that antibodies to IE surface antigens, particularly PfEMP1, play an earlier role in acquired immunity to malaria, whereas greater exposure is required for protective antibodies to merozoite antigens. These findings have implications for vaccine design and serosurveillance of malaria transmission and immunity. Abstract : Antibodies to surface antigens of P. falciparum ‐infected erythrocytes were associated with protection against symptomatic malaria in younger and older children, while antibodies to merozoite antigens were only protective in older children. PfEMP1 is the major target of antibodies to the surface of infected erythrocytes among children from Papua New Guinea